Gallium containing calcium phosphates: Potential antibacterial agents or fictitious truth. (15th September 2022) - Mosina, Marika; Kovrlija, Ilijana; Stipniece, Liga; Locs, Janis
Abstract: Amidst an ever-increasing demand for the enhancement of the lifestyle and the modulation of modern diseases, the functionalization of biomaterials is of utmost importance. One of the leading materials for the aforementioned purpose have been calcium phosphates (CaPs). They have been widely used in bone regeneration displaying favourable regenerative potential and biological properties. Many studies have placed their entire focus on facilitating the osteogenic differentiation of stem cells and bone progenitor cells, while the aspect of antibacterial properties has been surmounted. Nevertheless, increasing antibiotic resistance of bacteria requires the development of new materials and the usage of alternative approaches such as ion doping. Gallium (Ga) has been the potential star on the rise among the ions. However, the obstacle that accompanies gallium is the scarcity of research performed and the variety of amalgamations. The question that imposes itself is how a growing field of therapeutics can be further entwined with advances in material science, and how will the incorporation of gallium bring a new outlook. The present study offers a comprehensive overview of state-of-the-art gallium containing calcium phosphates (GaCaPs), their synthesis methods, antibacterial properties, and biocompatibility. Considering their vast potential as antibacterial agents, the need for a methodical perspective is highly necessary to determine if it is a direction on the brink of recognition or a fruitless endeavour. Statement of significance: Although several studies have been published on various metal ions-containing calcium phosphates, to this date there is no systematic overview pointing out the properties and benefits of gallium containing calcium phosphates. Here we offer a critical overview, including synthesis, structure and biological properties of gallium containing calcium phosphates. Graphical abstract: Image, graphical abstract